On the distribution of a rotationally invariant α-stable process at the hitting time of a given hyperplane - Osypchuk, M.M.; Portenko, M.I. (Reports of the National Academy of Sciences of Ukraine, 2018)
We find out an explicit formula for the distribution of a rotationally invariant α-stable process at that moment of time, when it hits a given hyperplane for the first time. The case of 1<α⩽2 is considered.